Impact of Obesity-Associated SARS-CoV-2 Mutations on COVID-19 Severity and Clinical Outcomes - Ana B. Martínez-Martinez; Alexander Tristancho-Baró; Beatriz Garcia-Rodriguez; Marina Clavel-Millan; Maria Pilar Palacian; Ana Milagro; Antonio Rezusta; Jose M. Arbones-Mainar (Viruses)
This study explores the relationship between specific SARS-CoV-2 mutations and obesity, focusing on how these mutations may influence COVID-19 severity and outcomes in high-BMI individuals. We analyzed 205 viral mutations from a cohort of 675 patients, examining the association of mutations with BMI, hospitalization, and mortality rates. Logistic regression models and statistical analyses were applied to assess the impact of significant mutations on clinical outcomes, including inflammatory markers and antibody levels. Our findings revealed three key mutations—C14599T, A20268G, and C313T—that were associated with elevated BMI. Notably, C14599T appeared to be protective against hospitalization, suggesting context-dependent effects, while A20268G was linked to a 50% increase in hospitalization risk and elevated antibody levels, potentially indicating an adaptive immune response. C313T showed a 428% increase in mortality risk, marking it as a possible poor-prognosis marker. Interestingly, all three mutations were synonymous, suggesting adaptive roles in obesity-driven environments despite not altering viral protein structures. These results emphasize the importance of studying mutations within the broader context of comorbidities, other mutations, and regional factors to enhance our understanding of SARS-CoV-2 adaptation in high-risk groups. Further validation in larger cohorts is necessary to confirm these associations and to assess their clinical significance.